Assessment of Atrial Natriuretic Peptide (ANP) Level and Relationship with Some Physiological Parameters - Wala’a Hassan Hadi; Khalid G. Al-Fartosi (University of Thi-Qar Journal of Science, 2021)
The present study investigated the level of atrial natriuretic peptide (ANP) and relationship with some physiological parameters of diabetic male rats induced by streptozotocin. Thirty male rats (Rattus norvegicus) were used in this study, and divided into five groups (6 rats for each group). Group1, considered as the negative group, given standard food and water for a period of 30 days. Group 2, served as the positive control (diabetic control), given streptozotocin 60 mg/kg b.w. as a single dose with standard food and water for 15 days. Group 3, received streptozotocin (60 mg/kg) with standard food and water for 15 days, then treated orally with foxiga 1mg/kg every day for a period of 15 days. Group 4, given streptozotocin (60 mg/kg) with standard food and water for 30 days. Group 5, received streptozotocin (60 mg/kg) with standard food and water for 30 day, then treated with foxiga1mg/kg administrated orally every day for a period of 15 day. The results indicated a significant increase (P<0.05) of glucose level in groups (2,3,4,5) compared with group (1). There was a significant decrease of glucose level in group (2) compared with group (3). But there was a significant increase of glucose level in group (3) compared with group (4). There was a significant decrease in group (4) compared with group (5). The results indicated .a significant increase (P<0.05) in atrial natriuretic peptide in groups (2,3,4,5) compared with group (1).There was no significant decrease in level of ANP in group (2) compared with group (3). There was significant increase in level of ANP in group (3) compared with group (4). But there was no significant decrease in group (4) compared with group (5). The result indicated a significant increase (P<0.05) in level of ALP in groups (2,3,4,5). There was no significant decrease in group (2) compared with group (3). ALP level significant increase in group (3) compared with group (4). There was no significant decrease in group (4) compared with group (5). The result indicated significant increase (P<0.05) of level ALT and AST in groups (2,3,4,5) compared with group (1). There was significant decrease in group (2) compared with group (3). ALT and AST levels were significant increase in group (3) compared with group (4). There was significant decrease in group (4) compared with group (5). The result indicated a significant increase (P<0.05) in level of ALP in groups (2,3,4,5). There was no significant decrease in group (2) compared with group (234) compared with group (5).